Modified Salter Pelvic Osteotomy for DDH treatment which may improve both anterior and posterior femoral head coverage. - Suvorov, Vasyl (2022)
Objective: Three pelvic osteotomies (Salter, Dega, Pemberton) are widely used in walking patients under 7 years old for DDH treatment. We’ve proposed a modified Salter Pelvic Osteotomy (SPO), which has the advantages of the abovementioned osteotomies. Methods: Short- and mid-term results were assessed in 19 patients after modified SPO application. Patients were examined before and after the surgery, at 6 months postoperatively and at follow-up. Results: Acetabular Index (AI) before the surgery was 39.5 ± 7 °, after the surgery - 24.4 ± 5.5 °, at 6 months - 20.4 ± 5 ° (9-28), at follow-up - 14.5 ± 4 °; AI correction - 14.9 ± 5.5 °. Lateral Centre-Edge Angle at follow-up - 22.7 ± 4.7 °. Clinical results at follow-up were I / II McKay grade in 18 patients (94.7%); radiological results were  I / II Severin class in 18 patients (94.7%). Conclusion: Modified SPO allows to improve the FH coverage in any direction; results after modified SPO are excellent and good in the vast majority of patients. Level of Evidence IV, Case Series